Peptidase PepP is a novel virulence factor of Campylobacter jejuni contributing to murine campylobacteriosis - Heimesaat, Markus M.; Schmidt, Anna Maria; Mousavi, Soraya; Escher, Ulrike; Tegtmeyer, Nicole; Wessler, Silja; Gadermaier, Gabriele; Briza, Peter; Hofreuter, Dirk; Bereswill, Stefan; Backert, Steffen (Gut Microbes, 2020)
Mechanisms of host–pathogen interactions resulting in immunopathological responses upon human Campylobacter jejuni infection are not completely understood, but the recent availability of murine infection models mimicking key features of campylobacteriosis helps solving this dilemma. During a screen for proteases expressed by C. jejuni, we identified a peptidase of the M24 family as a potential novel virulence factor, which was named PepP. The gene is strongly conserved in various Campylobacter species. A constructed deletion mutant ΔpepP of C. jejuni strain 81–176 grew as efficiently compared to isogenic wild-type (WT) or pepP complemented bacteria. To shed light on the potential role of this protease in mediating immunopathological responses in the mammalian host, we perorally challenged microbiota-depleted IL-10−/- mice with these strains. All strains stably colonized the murine gastrointestinal tract with comparably high loads. Remarkably, pepP deficiency was associated with less severe induced malaise, with less distinct apoptotic and innate immune cell responses, but also with more pronounced proliferative/regenerative epithelial cell responses in the large intestine at d6 post-infection. Furthermore, pro-inflammatory mediators were lower in the colon, ileum, and mesenteric lymph nodes of mice that had been challenged with the ΔpepP mutant compared to the WT or pepP complemented strains. This also held true for extra-intestinal organs including liver, kidneys, and lungs, and, strikingly, to systemic compartments. Taken together, protease PepP is a novel virulence determinant involved in mediating campylobacteriosis. The finding that apoptosis in the colon is significantly diminished in mice infected with the pepP mutant highlights the epithelial layer as the first and main target of PepP in the intestine.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Campylobacteriosis; host–pathogen interaction; M24 peptidase family; pepP; pro-inflammatory immune responses; secondary abiotic IL-10; Xaa-Pro aminopeptidase